Novel structurally similar chromene derivatives with opposing effects on p53 and apoptosis mechanisms in colorectal HCT116 cancer cells - Lima, Cristóvão Fernando Macedo (2015)
In the present work, novel chromene derivatives fused with the imidazo[1,2-a]pyridine nucleus were tested for their anticancer potential in the human colorectal cancer HCT116 cells. Compounds 2a and 2c showed significant growth inhibitory activity with GI50 of 15 mu M and 11 mu M, respectively. Compound 2c, the most potent, has a carbamate group in position 8 of the pyridine ring, and showed significant cell cycle arrest and induction of cell death by apoptosis, even at 51xM. Besides different potencies, chromene analogs 2a and 2c showed different mechanisms of action. Whereas the carbamate-free chromene 2a induced cell cycle arrest at GI /G0 phase, compound 2c showed to arrest cell cycle at both S and G2 phases. Chromene derivative 2a at concentrations higher than its GI50 remarkably induced caspases-dependent apoptosis in a p53-independent manner. On the other hand, compound 2c increased significantly p53 levels and induced apoptosis in a p53- and caspases-dependent manner, even at concentrations lower than its GI50. Both compounds increased the Bax/Bcl-2 ratio, induced mitochondria depolarization and activated MAP kinases. In conclusion, two novel and structurally similar chromene derivatives showed cytotoxicity to HCT16 cells through opposing effects on p53 levels and apoptosis mechanisms, which may be relevant for further development of drugs acting on distinct molecular targets useful in the treatment of cancers with different genetic profiles and for personalized medicine.